VD_FINDINFO Réc-administrative / 2014 / 8 vom 21. Oktober 2014 - VD Tribunal cantonal (2014)
RÉCUSATION, DROIT À UNE AUTORITÉ INDÉPENDANTE ET IMPARTIALE | 6 al. 1 let. a ROTC, 10 al. 2 LPA-VD, 11 al. 3 LPA-VD, 9 let. b LPA-VD, 8b al. 2 CDPJ